2013
DOI: 10.1002/cam4.59
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 5‐year imatinib treatment of 458 patients with CPCML in routine clinical practice and prognostic impact of different BCRABL cutoff levels

Abstract: We evaluated responses to the treatment and long-term outcomes of chronic myeloid leukemia patients treated with imatinib as first-line treatment in routine clinical setting from two countries with centralized tyrosine kinase inhibitors (TKIs) treatment. We assessed prognostic significance of European LeukemiaNet (ELN) 2006- and 2009-defined responses and the prognostic value of molecular responses at defined time points on 5-year survivals. Among the cumulative rates of incidence of hematologic, cytogenetic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…(2) In comparison, the percentage of CCyR and MMR among the patients in the present study was 80.0% and 65.7%, respectively, which are comparable to other studies. (15,16) Hence, the results of our study show that a good response can also be achieved in a real-life clinical setting.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…(2) In comparison, the percentage of CCyR and MMR among the patients in the present study was 80.0% and 65.7%, respectively, which are comparable to other studies. (15,16) Hence, the results of our study show that a good response can also be achieved in a real-life clinical setting.…”
Section: Discussionsupporting
confidence: 59%
“…This finding is consistent with the results published by Klamová et al, which showed that patients with a BCR-ABL level < 10% at six months had better survival. (16) Furthermore, Hughes et al also proved that BCR-ABL levels of > 10% at six months and > 1% at 12 months predict inferior EFS and a higher rate of disease progression. (2) This observation is especially important for less developed countries, where the need to use higher dosages of imatinib or the need to change treatment from imatinib to newergeneration TKIs (in order to achieve faster and deeper responses) would result in a significant financial burden.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that achievement of an early response is an important determinant for the outcome in CP‐CML patients treated with first‐line TKIs is not new; several authors have previously shown the importance of early response with respect to OS and progression‐free survival . In this study, our analysis showed that patients who did not achieve CCgR and patients with BCR‐ABL1 transcript levels > 10% at 3 months of imatinib therapy had lower CCI compared with patients who achieved a 3‐month CCgR or patients with BCR‐ABL1 transcript levels ≤ 10% at 3 months, respectively.…”
Section: Discussionmentioning
confidence: 50%
“…Therefore, cytogenetic examinations at 3 months of imatinib therapy were not available in some patients due to changes in the therapeutic recommendations for CML patients over the last decade. Regarding the analysis of BCR‐ABL1 transcript levels at 3 months, the BCR‐ABL1 transcripts were evaluated as internationally recommended ; patients with BCR‐ABL1 transcript levels ≤ 10% were compared to those with BCR‐ABL1 transcript levels > 10% . However, the BCR‐ABL1 transcript levels were available only in patients, whose samples were analyzed in three laboratories with the standardized quantitative real‐time RT‐PCR methodology at the time of data collection (annual quality control was provided by the National reference laboratory for DNA diagnostics in the Czech Republic).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation